Quaternary imidazolium-functionalized reactive silica nanoparticles-containing thiol-ene photocured antibacterial hybrid coatings - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (Elsevier B.V., 2022)
The need for antibacterial coatings is increasing day by day. In this study, coating materials that do not contain antibacterial agents but have antibacterial properties have been developed. First, two different quaternary imidazole compounds were synthesized. Then, silica nanoparticles were modified with these quaternary agents. By using 1%, 3% and 5% modified silica nanoparticles, UV cured coating materials were obtained according to the thiol-ene reaction mechanism. Mechanical, thermal, surface, structural, optical and antibacterial analyzes of the obtained coatings were performed. The analyzes revealed that UV cured antibacterial coating materials have been successfully synthesized and can be used as a new and unique coating material for the coating industry. © 2021 Elsevier B.V.
Keywords: Antibacterial coatings; Quaternary imidazole; Silica nanoparticles; Thiol-ene reaction; UV curing